Japanese multicenter prospective study investigating laparoscopic surgery for locally advanced rectal cancer with evaluation of CRM and TME quality (PRODUCT trial). Issue 6 (3rd July 2022) - Takemasa, Ichiro; Hamabe, Atsushi; Ito, Masaaki; Matoba, Shuichiro; Watanabe, Jun; Hasegawa, Suguru; Kotake, Masanori; Inomata, Masafumi; Ueda, Kazuki; Uehara, Kay; Sakamoto, Kazuhiro; Ikeda, Masataka; et al.
Abstract: Aim: In Japan, we have not been able to validate the results of laparoscopic surgery for locally advanced rectal cancer using the universal index "circumferential resection margin (CRM)." Previously, we established a semi‐opened circular specimen processing method and validated its feasibility. In the PRODUCT trial, we aimed to assess CRM in patients with locally advanced rectal cancer who underwent laparoscopic rectal resection. Methods: This was a multicenter, prospective, observational study. Eligible patients had histologically confirmed rectal adenocarcinoma located at or below 12 cm above the anal verge with clinical stage II or III and were scheduled for laparoscopic or robotic surgery. The primary endpoint was pathological CRM. CRM ≤1 mm was defined as positive. Results: A total of 303 patients operated on between August 2018 and January 2020 were included in the primary analysis. The number of patients with clinical stage II and III was 139 and 164, respectively. Upfront surgery was performed for 213 patients and neoadjuvant therapy for 90 patients. The median CRM was 4.0 mm (IQR, 2.1‐8.0 mm), and CRM was positive in 26 cases (8.6%). Univariate and multivariate analyses demonstrated that a predicted CRM from the mesorectal fascia of ≤1 mm on MRI was the significant factor for positive CRM ( P = .0012 and P = .0045, respectively). Conclusion: This study showed the quality of laparoscopic rectal resection based on the CRM in Japan. Preoperative MRI is recommended for locally advanced rectal cancer to prevent CRM positivity. Abstract : In this report, we validated circumferential resection margin (CRM) in patients with locally advanced rectal cancer who underwent laparoscopic rectal resection in a multicenter, prospective, observational study. This study showed the quality of Japanese laparoscopic rectal resection based on CRM for the first time, and MRI was demonstrated to be a crucial examination to predict positive CRM. These results would be quite significant in considering treatment strategy for locally advanced rectal cancer.